Perlawanan Sosial terhadap Korporasi untuk Pelestarian Lingkungan dari Eksplorasi Tambang: Social Resistance against Corporations for Environmental Preservation from Mining Exploration - Syafruddin Syafruddin; Hamidsyukrie Hamidsyukrie; Hairil Wadi; Yuliatin Yuliatin; Ulfatun Hasanah (Society, 2022)
Environmental preservation needs to be considered to avoid conflicts and social protests in the mining world, especially in the communities around the mines. Conflicts of social resistance and efforts to preserve the environment through protests to preserve the environment in West Nusa Tenggara. This research method is descriptive qualitative with a case study approach. The results of this research indicate that exploration permits without regard to sociological and ecological conditions cause social conflict. Furthermore, the form of social conflict is in the form of demonstrations and protests on a large scale by closing the main access to West Nusa Tenggara - East Nusa Tenggara, burning state facilities and social vulnerability. It is hoped that the results of this research are related to the policies and granting of mining business licenses to pay more attention to social problems.